Respuesta :

Answer:

A

Step-by-step explanation:

Given

x² - x = 30

To complete the square

add ( half the coefficient of the x- term )² to both sides

x² + 2(- [tex]\frac{1}{2}[/tex])x + [tex]\frac{1}{4}[/tex] = 30 + [tex]\frac{1}{4}[/tex]

(x - [tex]\frac{1}{2}[/tex])² = [tex]\frac{121}{4}[/tex]

Take the square root of both sides

x - [tex]\frac{1}{2}[/tex] = ± [tex]\sqrt{\frac{121}{4} }[/tex] = ± [tex]\frac{11}{2}[/tex]

Add [tex]\frac{1}{2}[/tex] to both sides

x = [tex]\frac{1}{2}[/tex] ± [tex]\frac{11}{2}[/tex], thus

x = [tex]\frac{1}{2}[/tex] - [tex]\frac{11}{2}[/tex] = - 5

x = [tex]\frac{1}{2}[/tex] + [tex]\frac{11}{2}[/tex] = 6

ACCESS MORE